1999
DOI: 10.1038/sj.bmt.1702016
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation for childhood myeloid malignancies after high-dose thiotepa, busulfan and cyclophosphamide

Abstract: Summary:Seventeen children with advanced myeloid malignancies (induction failure, relapse, myelodysplasia, secondary AML, or CR Ͼ1) received thiotepa 750 mg/m 2 i.v., busulfan 12 mg/kg or 640 mg/m 2 p.o., and cyclophosphamide 120 mg/kg i.v. as a preparative regimen for allogeneic or autologous hematopoietic stem cell (HSC) transplantation. Of the 15 allogeneic transplants, eight were from matched siblings, one was from a mismatched sibling, and six were from unrelated donors. Graft-versus-host disease (GVHD) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…Considering GVHD, most patients in this series received unrelated BMT, and the incidence of grade III-IV acute GVHD and chronic GVHD was similar to that in other reports. 25,26 As a result, the TRM rate of 21.5% was comparable to or lower than those reported in other studies 2,3,6 and the tolerability and safety of this regimen could be demonstrated. It is noteworthy that TRM occurred in only 1 patient among 11 patients who were not in remission at HSCT.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Considering GVHD, most patients in this series received unrelated BMT, and the incidence of grade III-IV acute GVHD and chronic GVHD was similar to that in other reports. 25,26 As a result, the TRM rate of 21.5% was comparable to or lower than those reported in other studies 2,3,6 and the tolerability and safety of this regimen could be demonstrated. It is noteworthy that TRM occurred in only 1 patient among 11 patients who were not in remission at HSCT.…”
Section: Discussionsupporting
confidence: 75%
“…1,2 In addition, the risk for TRM increases as the disease status at HSCT is advanced. [2][3][4] Although investigators have attempted to intensify the anti-leukemic effect by adding etoposide or thiotepa to conventional preparative conditioning regimens, such as TBI and CY or BU and CY, the disease-free survival (DFS) rates still do not significantly improve in patients with advanced disease. [3][4][5][6] The incidence of RP after HSCT still remains high.…”
Section: Introductionmentioning
confidence: 99%
“…26,28,34 Some alternative regimens have been used and reported but failed to strongly demonstrate advantage because of a too small cohort or a higher number of early relapse and regimen-related deaths. 29,32,[35][36][37] Much progress was done in the HSCT field from 1990s: improvement in HLA typing, improvement of supportive care, more available immunosuppressive drugs, improvement in laboratory cellular therapy settings, better understanding and monitoring of minimal residual disease. However, we have to continue our efforts and research in order to improve global results, that is, disease control and both acute and late side effect.…”
Section: Discussionmentioning
confidence: 99%
“…But pediatric conditioning regimens containing thiotepa were not reported to have an exceedingly high incidence of VOD. [30][31][32][33] Most recently a treatment regimen consisting of cyclophosphamide, thiotepa and carboplatin was assessed for the occurrence of VOD in adults. The calculated plasma concentration-time curves (AUCs) for cyclophosphamide and its activated metabolites showed that the incidence of VOD was rather linked to bioactivated cyclophosphamide than to the administration of thiotepa.…”
Section: Discussionmentioning
confidence: 99%